Introducing the ProInterest model - Laura Tuohilampi; Huifei Jiang (LUMAT)
This study introduces the ProInterest model, a novel framework designed to foster long-term student engagement in mathematics. ProInterest model identifies features that trigger initial interest and subsequently sustain student interest towards mathematics activities. We explore the interplay between these features based on a focused narrative review and demonstrate their application through a case analysis of two mathematics tasks that look different on the surface, yet can be identified to share common features fostering interest when looked through the lense of the ProInterest model. We also apply the model to tasks generated by experts and AI. We show that applying the model to identify features that can trigger and maintain student interest towards a task, one can reveal shortcomings in typical mathematics tasks: humour and creativity are typically missing, and even tasks aimed to be tailored to appeal to students may utilise unimaginative layout and structure. This research bridges a critical gap in the knowledge of interest promoting mathematics tasks by providing a practical tool for educators and instructional designers to create engaging mathematics experiences.